2018
DOI: 10.2147/ndt.s186209
|View full text |Cite
|
Sign up to set email alerts
|

Elevated circulating magnesium levels in patients with Parkinson’s disease: a meta-analysis

Abstract: BackgroundThe association between circulating magnesium (Mg) and Parkinson’s disease (PD) remains ambiguous and controversial. Thus, a meta-analysis was conducted to evaluate the circulating Mg levels in PD patients and to clarify whether high circulating Mg levels should be considered as a potential risk factor for PD.MethodsIn this study, 17 case–control published studies were selected in our meta-analysis by searching the electronic databases of Web of Science, PubMed, and China National Knowledge Infrastru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Similarly, Mg plays a significant role in neuromuscular signal conduction, energy synthesis, and releasing neurotransmitters ( Oyanagi et al, 2006 ). Significant increase in Mg was noticed in our study; a similar result was noticed in the meta-analysis of Jin et al (2018) . Additionally, this result was further supported by our previous study ( Ahmed and Santosh, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Mg plays a significant role in neuromuscular signal conduction, energy synthesis, and releasing neurotransmitters ( Oyanagi et al, 2006 ). Significant increase in Mg was noticed in our study; a similar result was noticed in the meta-analysis of Jin et al (2018) . Additionally, this result was further supported by our previous study ( Ahmed and Santosh, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Mg 2+ concentration in the cerebrospinal fluid of PD patients decreased with the duration and severity of the disease [11]. However, circulating Mg 2+ levels in PD etiology remain controversial, a study indicated PD patients tendend towards elevated circulating magnesium levels [48]. Epidemiological results support the possibility that mutations in genes relevant to magnesium homeostasis would alter PD risk [16].…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses showed that deficiency and insufficiency of vitamin D were positively associated with PD development (deficiency and insufficiency, pooled OR: 1.50, 95% CI: 1.31 to 1.71, I 2 = 55.9%, 6 case-control, cohort, and cross-sectional studies; deficiency, pooled OR: 2.08, 95% CI: 1.35 to 3.19, I 2 = 84.7%, 10 case-control, cohort, and crosssectional studies; insufficiency, pooled OR: 1.73, 95% CI: 1.48 to 2.03, I 2 = 31.0%, 6 case-control, cohort, and cross-sectional studies) [45,60]; no subgroup analysis based on study design was conducted (Supplementary Table 1). Pooled results of casecontrol studies showed that PD patients had lower levels of serum uric acid, serum BDNF, and serum iron and higher circulating Mg and CRP levels [34,59,62,63]. No significant association between LDL-C and PD development was found (pooled RR: 0.58, 95% CI: 0.31 to 1.07, I 2 = 71.0%, 3 case-control and cohort studies) [52] (Supplementary Table 1).…”
Section: Biomarkersmentioning
confidence: 99%